Fyre - Sage, Angie (Bloomsbury London, 2013)
Septimus Heap, Wizard Apprentice, must fight the remnants of the Darke Domaine. For this, the ancient Alchemie Fyre must be re-lit, a task which will test Septimus to his limits and send him on a perilous journey. Septimus will finally discover who he is -- but at what cost? And who will prevail when the greatest Magyk of all is kindled? Prepare for a spellbinding finale, as FYRE masterfully weaves together every character from this epic series